HIV/AIDS: IT’S MEDICOLEGAL AND SOCIAL ASPECTS (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
In recent years, acquired immunodeficiency Syndrome has emerged as the biggest ever threat to humanity all over world. Rapid spread of this dreaded killer viral disease has inflicted great terror in the minds of people all over the world. HIV, the etiological agent of AIDS, belongs to the lentivirus subgroup of the family retroviridae & has no cure as yet. There are many medical, legal & social problem arises due to HIV infection. There is an active debate in India on the legal & social rights of HIV/AIDS patient. Efforts to protect individual rights while safeguarding the public from a fatal virus are presenting many legal questions on public health, education, employment, insurance, widow pension, medical law, family law, criminal & civil law etc. There are also many social questions prevailing like blaming to the patient, ignorance, prejudice, discrimination, stigmatization etc.The existing AIDS law in India consists of state amendments and a proposed central bill. In August 1989 a bill was proposed in the parliament called the AIDS prevention bill.
Keywords: Human immunodeficiency virus (HIV); AIDS